Peran Mediasi Loyalitas Pelanggan: Harga dan Promosi Terhadap Keputusan Pembelian Pada Merek Kosmetik Wardah Dikota Samarinda - Risal, M.; Tiara; Putri , Selma Riana; Aprialdi , Muhammad (Universitas Muhammadiyah Pontianak, 2026)
This study investigates the effects of price and promotion on purchase decisions for Wardah cosmetics in Samarinda, with customer loyalty as an intervening variable. Using a quantitative survey of Wardah consumers and PLS-SEM, the results show that price does not significantly influence purchase decisions, whereas promotion has a positive and significant effect. Both price and promotion significantly affect customer loyalty, but loyalty does not significantly influence purchase decisions and does not mediate the effects of price or promotion. These findings indicate that promotional strategies are more critical than pricing strategies in driving Wardah purchase decisions.